Cytoflavin® Effect on Endothelium Function and Cerebral Hemodynamics in Patients with Hypertensive Enceplalopathy - L. A. Belova; V. V. Mashin; O. Yu. Kolotik-Kameneva; A. N. Proshin (Антибиотики и Химиотерапия, 2020)
One hundred forty patients (the average age of 46.7±7.7 years) with hypertensive encephalopathy (HE) were observed. 74 patients of the main group received Cytoflavin® in a dose of 2 tablets twise a day in the standard basic therapy. 66 patients of the reference group received the basic therapy alone. The arterial endothelium function was estimated and ultrasonic examination of the hemodynamics at five structurally functional levels of the cerebral vascular course was used. All the patients with HE had endothelial dysfunction, bloodstream depression in the arterial course of the brain vascular system, decreased reactivity of the intracranial veins, difficulty in venous outflow. In the course of the therapy with Cytoflavin® restoration of the arterial endothelial function in the patients with HE I stage, the linear and volume speed of bloodstream in the main and intracranial cerebral arteries in the patients with HE I-II stages, restoration of the intracranial veins reactivity, the linear speed of bloodstream in intracranial veins in the patients with all three stages of HE, the linear speed of bloodstream in the main veins up to the control values in the patients with I-III stages of HE were observed. Interrelation between the values of the cerebral hemodynamics and the state of the endothelium function was shown.